Influência da zircônia no arrefecimento de brocas para implantes osseointegráveis: ensaio mecânico - Souza, Edmo Matheus Rocha de (2015)
Specimens were made from bovine ribs and milling divided into two groups (A - B mills in steel - mills in zirconia), each group was divided into four subgroups according to different settings milling (rotation and pressure milling). They were measured and compared the temperatures of the milling burs made by the two materials made using four different configurations. A prosthetic surveyor has been adapted to the study to connect a surgical electronic engine, counter angle driver for implants. A container was also coupled to one of the liner's arms to accommodate components metallic spheres of standard weight, sometimes 1.2kg, 2.4kg moment according to the configuration of each subgroup such that the surgical motor that ran milling in 1000 and 2000 rpm. In order to measure milling temperatures, they used two thermocouples of the same make and model in two depths milling, the first and the second 5mm to 15mm. All the cutters are subjected to washing and antisepsis every two tests. The heat generated by the friction between bone and surgical instrumentation during such drills tend to be imparted to this tissue degeneration resulting protein that cause scarring and can be decisive in higher failure rates. Several factors are potentially destined to contribute to increasing the temperature for the osteotomies of which insufficient irrigation, using worn drills, surgical instrumentation outside the standard suggested by the manufacturer and the material constituting the object of this study surgical drills.